Active vs intuitive sensemaking: Examination through the lens of generation, evaluation, and revision in ethical decision-making. Issue 4 (19th May 2021) - Gujar, Yash; Higgs, Cory; Sanders, Chanda; Fichtel, Mark; McIntosh, Tristan; Turner, Megan R.; Connelly, Shane; Mumford, Michael D.
ABSTRACT: Research examining ethical decision-making (EDM) has focused on how people engage in EDM, leading many researchers to focus on sensemaking models of EDM. Although the merits of a sensemaking approach with respect to EDM are evident in the literature, less is known about the specific cognitive processes by which sensemaking impacts EDM. This study examines the impact of three late-cycle cognitive processes – idea generation, evaluation, and revision – as well as the timing of these processes on EDM. Results indicate that information gathering early on is critical to EDM; a finding which supports an active sensemaking model over an intuitive one.